CODE MIXING USED IN VIDEO PODCAST OF BOY WILLIAM’S YOUTUBE CHANNEL - Eripuddin; Donal, Andri; Jumisa, Siti (JEE (Journal of English Education), 2023)
The purpose of the research aimed to know the code mixing found in video podcast on boy William’s YouTube channel. the purpose of this study is to the kinds of code mixing used in video podcasts on boy William’s YouTube channel and what are the reasons Boy William used code mixed video podcasts on his YouTube channel.this study used a qualitative descriptive research method. The researcher analyzes the kinds of code mixing used in the video podcast on boy William’s YouTube Channel with the title: Chef Renata, the original difference is the same on TV and Reza Rahardian’s career from extras to becoming a famous actor. Then, to analyze the data, the researcher used the components of code mixing such us: insertion, alternation, and congruent lexicalization. The result of this research is shows that the kinds of code mixing that the researcher used in the video Chef Renata Asli is the same as on TV there are 9 insertion utterances, 3 substitution utterances, and 2 congruent lexicalization utterances. 2 insertion utterances, 2 insertion utterances, and 3 congruent lexicalization utterances.